2020
DOI: 10.18502/ijph.v49i11.4716
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma in the Treatment of Severe COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: COVID-19 is a public health emergency of international concern. Its incidence rates and mortality are very high; however, so far, an effective drug treatment remains unknown. Based on the role of convalescent plasma therapy in previously identified viral pneumonias, patients with severe COVID-19 have been given this therapy. This systematic review and meta-analysis aimed to summarize the clinical evidence regarding the efficacy and safety of convalescent plasma therapy in the treatment of severe CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We identified almost a hundred eligible trials that evaluate evidence on convalescent plasma treatment in patients with COVID-19. Among 21 other systematic reviews and meta-analyses on this topic that were available on PubMed as of mid-April, 2021 [ 5 , 46 , 47 , 51 68 ], 15 include only 0 to 2 randomized trials alongside observational studies (e.g., two LSR) [ 46 , 47 , 51 63 ] and the two most comprehensive reviews included 10 RCTs [ 5 , 64 ]. One of the latter meta-analyses [ 5 ] does not include the RECOVERY Trial and includes one trial that we categorized as non-randomized [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified almost a hundred eligible trials that evaluate evidence on convalescent plasma treatment in patients with COVID-19. Among 21 other systematic reviews and meta-analyses on this topic that were available on PubMed as of mid-April, 2021 [ 5 , 46 , 47 , 51 68 ], 15 include only 0 to 2 randomized trials alongside observational studies (e.g., two LSR) [ 46 , 47 , 51 63 ] and the two most comprehensive reviews included 10 RCTs [ 5 , 64 ]. One of the latter meta-analyses [ 5 ] does not include the RECOVERY Trial and includes one trial that we categorized as non-randomized [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is reported in Figure 1 . After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 SRs included in the overview, 26 were focused exclusively on COVID-19 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], while three were focused on respiratory pandemics and on beta coronaviruses infections [ 10 , 19 , 30 ]. Two SRs [ 17 , 22 ] were a subgroup analysis of other reviews [ 16 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that convalescent plasma did not improve clinical symptoms but reduced the risk of death in patients with severe infections [7]. A meta-analysis by Zhang and Sun et al incorporating observational and retrospective studies came to a similar conclusion that convalescent plasma reduces the risk of death in patients with severe infections [26,27]. However, recent RCT studies have found that convalescent plasma did not improve the prognosis of patients with severe disease [9,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%